2017
DOI: 10.24912/je.v20i2.164
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Struktur Kepemilikan Terhadap Kinerja Perusahaan Pada Sektor Keuangan Yang Tercatat Di Bursa Efek Indonesia Pada Tahun 2007-2010

Abstract: This research examine the effect of insider ownership and institutional ownership on corporate performance on  financial sector that listed in Indonesia Stock Exchange on 2007-2010.There is 11th  banking on this sample with multiple purposive sampling criteria. Research data was collected from Indonesian Capital Market Diectory. This research findings are insider ownership  significant effected  operational expenses to operational income  ratio and Loan to deposit ratio. But this failed to examine that institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…For digital banking variables, there were also differences, (Yultiara, 2018) proving that internet banking had no significant effect on ROA, while Arofany & Tandika (2017) stated that internet banking has a positive and significant effect on ROA. And according to S. Dedeh Sri & S. Nana (2018) mobile banking had an insignificant negative effect on ROA.…”
Section: Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…For digital banking variables, there were also differences, (Yultiara, 2018) proving that internet banking had no significant effect on ROA, while Arofany & Tandika (2017) stated that internet banking has a positive and significant effect on ROA. And according to S. Dedeh Sri & S. Nana (2018) mobile banking had an insignificant negative effect on ROA.…”
Section: Previous Researchmentioning
confidence: 99%
“…Previous researchers such as (Arofany & Tandika, 2017) stated that internet banking had a positive and significant effect on ROA. According to S. Dedeh Sri & S. Nana (2018) mobile banking had an insignificant negative effect on ROA. Judging from previous research which was still inconsistent, it was necessary to re-examine and because there was no digital banking research on zakat yet, it was examined by this research.…”
Section: The Influence Of Digital Banking On Profitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Beberapa perusahaan telah kehilangan kepercayaan investor, akibatnya perusahaan tersebut berada dalam fase financial distress atau kesulitan keuangan sehingga harus didelisting. Menurut Hastuti (2014) financial distress diartikan sebagai suatu keadaan dimana perusahaan mendekati kebangkrutan. Menurut Platt dan Platt dalam Yusbardini & Rashid (2019) financial distress merupakan kondisi yang menunjukkan bahwa keuangan perusahaan sedang krisis dan tidak sehat.…”
Section: Pendahuluanunclassified
“…Previous studies have shown inconsistent and mixed results because some researchers have observed that the impact is negative, and others have observed a positive impact and some even show that the results have no effect. A research by Sudaryanti et al (2018) shows that there is a negative influence between electronic banking on banking financial performance, while Kustina et al (2020) and Rebecca (2020) shows that there is a positive influence between the implementation of electronic banking on the performance of Indonesian banking. These results contradict the study by Thio (2021) andEl Chaarani &El Abiad, (2018) which shows that ebanking has no significant effect on the financial performance of the banking sector.…”
Section: Introductionmentioning
confidence: 99%